Representasi Peran Perempuan dan Kesetaraan Gender dalam Iklan Skincare Forebie - Muhammad Adnan Sukhfi; Rafi Hadrian Pratista; Erwan Sudiwijaya (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2025)
Abstract This study examines the representation of women's roles and gender equality in Forebie skincare advertisements on social media platforms, particularly Instagram and TikTok. While women's representation in advertising has historically been constrained by gender stereotypes, the emergence of feminism and "femvertising" trends has led to more diverse and empowering portrayals. Using a qualitative approach with a case study design, this research analyzes how Forebie communicates gender equality messages through visual and narrative elements in their advertisements. Through semiotic analysis of images, text messages, symbols, and overall advertising tone, the study evaluates whether Forebie perpetuates traditional gender stereotypes or offers a more progressive perspective. The findings reveal a complex interplay between commercial interests and gender representation, where Forebie shows potential for promoting more inclusive narratives while still occasionally reinforcing traditional beauty standards. The analysis identifies opportunities for local brands to utilize social media in advancing gender equality discourse, though challenges remain in balancing market demands with progressive representation in Indonesia's traditional social context.